BILIBILI data - Qinli Tang (19749543) (2025)
The table contains 300 video content records across 8 categories such as Game, Music, Film & TV, Knowledge, Technology, and Entertainment. Each record includes 13 dimensions of data, covering basic playback metrics, user engagement metrics, title characteristics, and visual design elements, to analyze the correlation between content dissemination and visual presentation.